Hubungan Kepemimpinan dan Manajerial Kepala Sekolah serta Kemampuan Teknologi terhadap Kinerja Guru SMK di Kecamatan Rappocini - Hartini Ramli (Sakura Digital Nusantara, 2023)
This research aims to examine the relationship between leadership and managerial skills of the school principal, technological competence, and the performance of vocational high school (SMK) teachers in Rappocini District. The research is conducted to understand how these factors interact and influence teachers' performance. The research method used is quantitative, with a sample size of 87 respondents. The data analysis employed multiple regression analysis with the assistance of IBM SPSS software. The independent variables in this study are: (1) School Principal's Leadership (X1), (2) School Principal's Managerial Skills (X2), and (3) Teachers' Technological Competence (X3). The dependent variable is Teachers' Performance (Y). The results of the study indicate that the competence of leadership and managerial skills of the school principal has a positive and significant impact on teachers' performance in SMK. However, teachers' technological competence does not significantly affect their performance. The multiple linear regression analysis shows that all dimensions of the school principal's managerial competence, including effective communication, effective leadership, human resource management, self-development, and innovation, have a significant relationship with teachers' performance in SMK, with a success rate of 89.9%.